Failed umbilical artery catheterization and adverse outcomes in extremely low birth weight infants. (2nd November 2019) - Wallenstein, Matthew B.; Shaw, Gary M.; Yang, Wei; Stevenson, David K.
Abstract: Purpose: To determine whether successful catheterization of the umbilical artery is associated with a reduced risk of death or neurodevelopment impairment among critically ill extremely low birth weight (ELBW) infants. Study design: A retrospective chart review was conducted between 2007 and 2014 at Stanford University for all ELBW infants that required intubation immediately after birth. The primary outcome was death or neurodevelopmental impairment at 18–22 months. We measured the association of successful umbilical artery catheterization with the primary outcome using multivariable logistic regression with adjustment for gestational age. Bayesian analysis was also performed due to small sample size. Results: Eighty-four ELBW infants met inclusion criteria. Successful umbilical artery catheterization occurred in 88% of infants and failed catheterization in 12%. Death or neurodevelopmental impairment occurred in 41% of infants with successful catheterization, compared to 60% of infants with failed catheterization of the umbilical artery, adjusted odds ratio 0.3, 95% confidence interval 0.1–1.3, p  = .11. The Bayesian analysis indicated a 92% posterior probability of reduced death or neurodevelopmental impairment with successful catheterization and a 68% posterior probability of reduced death or neurodevelopmental by absolute risk difference of 20% or more, adjusted relative risk 0.74, 95% confidence interval 0.45–1.14. Conclusions: Among critically ill ELBW infants, successful catheterization of the umbilical artery compared to failed catheterization was not statistically significantly associated with the primary outcome. However, the Bayesian analysis indicated a high likelihood of benefit associated with successful umbilical artery catheterization.